Habilidades práxicas orofaciais pré e pós-terapia em crianças com desvio fonológico - Gubiani, Marileda Barichello (2011)
Approximately between 4 or 5 years of age, the child has already acquired all the phonemes of the adult phonological system. However, this process does not always occur according to expectations, being noted separations/deviations in the acquisition of speech sounds. In order to the speech to take place properly, it is necessary the minimal of structural development from the vocal tract and motor skills, and it is important that phonetic-articulatory and praxis issues are always investigated. This study aimed to verify the evolution of phonological, praxis and generalization of children with phonological deviation submitted to phonological therapy associated with the stimulation of oral praxis skills. The sample was composed of six subjects (three girls and three boys) aged between 5:4 and 7:0 at the beginning of therapy. The subjects were divided in three groups, all receiving phonological therapy, being that in one group was added praxis stimulation of face and tongue (GFoLFa), and tongue praxis stimulation (GFoL) in another, the third group was submitted only to phonological therapy (GFo). All were evaluated before and after therapy regarding: phonological system (Yavas, Hernandorena and Lamprecht, 1991); Orofacial Praxis Test (Bearzotti, Tavano e Fabbro, 2007) and Bucofacial Articulatory Praxis test (Hage, 2000). The results were analyzed descriptively by comparing the three groups. The results evidenced that all groups presented evolution in the phonetic inventory, the GFoLFa obtained bigger evolution in the PCC-R, in the oral praxis skills and a larger number of generalizations (in the four analyzed types). Still, GFoL achieved considerable developments regarding oral praxis skills within a class of sounds, and GFo presented generalization to another class of sounds. This way, new ways of study applying this model are suggested, so that these results can be confirmed.